Evidence of Magnetic Correlations Among the Charge Stripe Electrons of Charge-Stripe Ordered La2NiO4.11 - Freeman, P; Hayden, S; Mole, R; Enderle, M; Prabhakaran, D; Boothroyd, A (2011)
The magnetic excitations of charge-stripe ordered La2NiO4.11 where investigated using polarized- and unpolarized-neutron scattering to determine the magnetic excitations of the charge stripe electrons. We observed a magnetic excitation mode consistent with the gapped quasi-one-dimensional antiferromagnetic correlations of the charge stripe electrons previously observed in La(2-x)Sr(x)NiO(4) x = 1/3 and x = 0.275.